A Case Study on BHL Bank at the Cross Roads - Lim, Joshua Yoke Long (1998)
'In 27 July 1997, " Thailand market crashes" this was quoted in the New Straits Times. The paper reported that the crash in 1JJaiJand has ca.used panic to foreign fund managers in the ASEAN region. Paul Sager, one of the Investment Manager ca/ls, Datuk Goh requesting some insight as to the recent turmoil happening in the region. "We are getting jittery and the sentiment seems to be fear of a domino effect on the local KLSE" said Paul. "There were reports by large hedge fund managers speculating that there are fundamental weakness in ASEAN and Malaysian economy" adds Paul. Datuk Goh asked Paul's opinion how he and the rest of the fund manager view the Malaysian economy. Paul Sager indicated that the region would be heading for a tough time as the foreign investment community feels there are fundamental weakness especially in the financial system which have yet to be rectified. There were heavy selling on Malaysian currency causing the exchange rates to be devalued by at least 60% as concerns on the Malaysian property sector bursting. There are worries of the Malaysian economy overheating" explains Paul. Paul suggested to Datuk Goh whether he has any plans to to cope with the impending pressures. 1JJe next morning on the 28 July 1997, Datuk called for an emergency Board meeting to discuss on the report he receives. Datuk Goh was especially interested with the figures relating to the loans made to large conglomerates, which have heavy interests in properties. He also wanted to know the actual loans made and the details of the any substantial project the banks are involved directly or jointly finance. Neoh Choo Kean the General Manager of the Bank, reported that BHl Bank has no large loans more than 10 million exposures to any one corporate and they have always finance projects that are near Klang Valley and Urban 81'Cas. Datuk Goh was also interested in the exposure on sh81'C financing. Datuk directed Mr. Neoh to cut down on the lending and imposed on other forms of collateral. "There is need for a clear direction and evaluate our strengths and weakness for us to understand what the chal1enges facing our bank and industry Said Datuk Goh after the reporting. "BHL Bank needs to chart its path clearly and this requires participation by the top management and every employee of the bank. Continue Datuk Goh. independent consultant to be appointed analyzing BHL Banks current situation and identify the possible alternatives as to how best BHL Bank to grow in the board meeting." mooted Datuk The meeting was adjourned On the 5th December 1997, after a detail screening process, the Board decided to engage Mr. Joshua lim as the independent consultant. On 15th January 1998, Bank Negara Malaysia announced that there was three financial institution needing re-capitalization. It was also reported that Sime Bank had suffered RM1.18 billion. On the 2nd February 1998, Bank Negara identified anchor companies for consolidation of the finance companies quoted the Investor Digest February issue. It was reported in that issued Bank Negara Directives was for the finance companies to merger in view of the crisis hitting the banking sector. With an environment of tight liquidity, the banks have to form larger and stronger finance companies. "Said the editor of the Investor Digest February's issue. On the 20th Febrary 1998, Datuk Goh summon Joshua Lim and asked me to begin work immediately taking into account the current scenario and come out with a strategic paper for the Bank. Chairman directives was to study the feasibility of these alternatives and select the best option available to the bank taking into consideration of the internal and external factors surrounding BHL Bank.